Idiopathic Osteosclerosis of the Jaw in a Brazilian Population: a Retrospective Study - Elen de Souza Tolentino; Paulo Henrique Capel Gusmão; Guilherme Saintive Cardia; Lívia de Souza Tolentino; Lilian Cristina Vessoni Iwaki; Pablo Andrés Amoroso-Silva (University of Zagreb. School of Dental Medicine, 2014)
Objectives: To report cases of idiopathic osteosclerosis (IO), to review the literature on the subject, and to discuss its main characteristics, diagnosis, differential diagnosis, and treatment. Material and methods: Retrospective analysis of 354 panoramic radiographs, searching for IO, its size, shape, location, and noting patients' demographic information. Literature review used Medline and Lilacs databases and the terms idiopathic osteosclerosis OR bone sclerosis OR dense bone island AND jaws. Results: IO was identified in 5.6% of the radiographs (n=20 patients, 22 foci). Patients were healthy, with an age ranging from 5 to 51 years (mean=29.8), with male-female ratio of 3:2. IOs were found mainly in the premolar/molar region, at root apices, between roots, away from the teeth, laterally to the tooth, and in edentulous areas. The distribution between right and left sides of the jaw was equal for the 22 foci, with only one case in the maxilla. IOs were localized, well-defined, radiopaque, mostly round or ovoid in shape, but sometimes irregular. In some cases, IOs were similar to condensing osteitis, but differential diagnosis also considered complex odontoma, focal cemento-osseous dysplasia, and residual roots. Twenty studies on the topic were reviewed. Conclusions: Incidence of IO in the Brazilian sample was 5.6%, with age ranging from 5 to 51 years (mean=29.8), and male-female ratio of 3:2. The radiopacities occurred in different locations, with significant prevalence in the mandible. The findings and the literature review corroborate the hypothesis that IO should be considered developmental variation of normal bone that does not require treatment.